Prevalensi dan Distribusi Penderita Stomatitis Aftosa Rekuren (SAR) di Klinik Penyakit Mulut RSGM FKG Universitas Jember pada Tahun 2014 (Prevalence and Distribution of Patients Recurrent Aphthous Stomatitis ( RAS ) in Oral Medici - Annisa Sulistian; Sri Hernawati; Ayu Mashartini P (Pustaka Kesehatan, 2016)
Background: Recurrent Aphthous Stomatitis (RAS) is a disorder characterized by recurring ulcers confined to the oral mucosa with no other signs of disease. RAS is classified according to three classification, there are RAS minor, RAS mayor, and RAS herpetisformis. RAS prevalence of general population ranges from 5%-66%. Purpose: This study aimed to obtain the prevalence and distribution of patients suffering from RAS in Oral Medicine Departement of Dental Hospital, Dentistry Faculty, University of Jember in 2014. Method: This study used descriptive study with retrospective approach and purposive sampling. The population of this study is all patients of Oral Medicine Departement of Dental Hospital, Dentistry Faculty, University of Jember in 2014 as many as 1073 peoples. Result and Conclution: The result showed that 146 patients suffer SAR (14%) from 1037 patients in Oral Medicine Departement of Dental Hospital, Dentistry Faculty, University of Jember on January until December 2014. There were 97% of patients had RAS minor, 3% of patients had RAS mayor, and 0% of patients had RAS herpetisformis from 146 patients with RAS. RAS can occur in women or men and children or adults, the result of this research showed that RAS was most common in women, that was 70% and the age groups of 12-24 years was 54%. Keywords: Distribution, Prevalence, Recurrent Aphthous Stomatitis (RAS)